IMPLEMENTASI MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA PGSD - Kardiana Metha Rozhana; Moh. Farid Nurul Anwar (Universitas Tribhuwana Tunggadewi, 2021)
The purpose of the research was to implemented Problem based Learning (PBL) media in improving student learning outcomes in the PGSD Study Program, Tribhuwana Tunggadewi University. This type of research used CAR (Classroom Action Research) by reviewing research in the form of descriptive. This research procedure was carried out for two cycles with the stages of planning, implementing, and reflecting. The stages was carried out with: 1) the planning stage by drawing up a Learning Implementation Plan and lecture contracts, preparing media, materials, and instruments; 2) the Action Stage is carried out in accordance with the RPS that has been prepared; 3) the observation and evaluation stages are carried out during the learning process and carry out documentation during the learning process in the classroom; 4) the reflection stage, namely analyzing the previous process, both its weaknesses and strengths. Learning outcomes in cycle 1 showed the percentage of 66% of students who did not complete their studies. And in cycle 2 there are 90.9% of students who complete learning. It can be concluded that the Problem Based Learning Model is very effective in improving the cognitive aspects of students.